2019
DOI: 10.1038/s41598-019-41997-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Energy Depletion by Metformin or Hypocaloric Diet on Thyroid Iodine Uptake in Healthy Volunteers: a Randomized Trial

Abstract: Sufficient thyroid iodine uptake is needed to ensure effective radioactive iodine (RAI) treatment, which is mediated by the sodium-iodide symporter (NIS). Activation of AMP-activated-protein-kinase (AMPK), leads to decreased NIS expression and thyroid iodine uptake in in vitro and animal models. Clinically relevant conditions that lead to AMPK activation include metformin use and hypocaloric conditions. Here, we aim to assess the effects of metformin and hypocaloric diet on thyroid iodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Zn alone or combined with Se might also influence thyroid function, where mean serum-free T3 increased significantly [36]. Researchers enrolled 15 healthy male volunteers, suggesting that T3 and T3/rT3 ratios decreased after hypocaloric diet or metformin supplementation [37]. Jane Teas et al found seaweed supplementation led to a higher TSH level, while soy supplementation did not influence thyroid function end points [38].…”
Section: Discussionmentioning
confidence: 99%
“…Zn alone or combined with Se might also influence thyroid function, where mean serum-free T3 increased significantly [36]. Researchers enrolled 15 healthy male volunteers, suggesting that T3 and T3/rT3 ratios decreased after hypocaloric diet or metformin supplementation [37]. Jane Teas et al found seaweed supplementation led to a higher TSH level, while soy supplementation did not influence thyroid function end points [38].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the influence of metformin on thyroid function, a clinical study has recruited 19 healthy male volunteers, showing that metformin does not alter iodine uptake in the thyroid gland [ 219 ]. However, various clinical studies performed in hypothyroid subjects have shown that metformin reduces thyrotropin (TSH) levels even if the mechanism involved is not fully understood [ 220 , 221 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, it is important to review the temporal nature of changes in rT3 levels. Prior studies show that following weight loss through diet or bariatric surgery, rT3 levels increase significantly by 2-3 weeks [8,43] and regress towards baseline levels by 3 months post-surgery [8]. To reduce participant burden, the current study accepted rT3 labs collected at any time over the entire 2 week to 3-month post-surgery time period.…”
Section: Discussionmentioning
confidence: 99%